Symptom clusters in head and neck cancer patients with endotracheal tube: Which symptom clusters are independently associated with health-related quality of life?. (October 2020) - Li, Yuanyuan; Li, Xiaoshuang; Mao, Cui; Lv, Gaorong; Xie, Zihui; Jiang, Hua; Li, Ping
Abstract: Purpose: The point of view of symptom clusters (SCs) may develop an efficient symptom management strategy to enhance health-related quality of life (HRQoL) in head and neck (HNC) patients with endotracheal tube (ETT). The study aims to investigate the possible SCs in HNC patients with ETT and determine whether there was an independent relationship between one or more SCs and HRQoL. Methods: A cross-sectional study design was adopted, and 203 HNC patients with ETT were recruited. They took measurements of General Information Questionnaire, MD Anderson Symptom Inventory-Head & Neck, and Twelve-Item Short-Form Health Survey (SF-12). Spearman correlations, partial correlations, and hierarchical cluster analysis were performed to determine latent number of SCs, and covariance analyses were used to determine independent associations between SCs and SF-12. This study followed STROBE Statement. Results: Pain SCs (pain, distressed, short of breath, and sadness), fatigue SCs (fatigue/weakness, restless, and sleepy), digestive SCs (appetite loss, constipation, and nausea), HNC-specific SCs (dry mouth and mucus), and tracheostomy-related SCs (difficulty swallowing and difficulty with voice and speech) were found. After adjusting covariant variables, this study found independent relationships of pain SCs and fatigue SCs with physical component summary of SF-12, and between fatigue SCs and mental component summary of SF-12. Conclusions: Multiple SCs were found in those HNC patients. Pain SCs and fatigue SCs were independently associated with HRQoL. In process of caring HNC patients with ETT, it is vital to focus on SCs, especially on pain SCs and fatigue SCs, which might effectively improve patients' HRQoL. Highlights: HNC patients with ETT had multiple symptoms presented simultaneously. Five SCs (pain, fatigue, digestive, HNC-specific, and tracheostomy-related SCs) existed in HNC patients with ETT. Independent associations between pain SCs and PCS of SF-12, and between fatigue SCs and PCS as well as MCS of SF-12.